Uncertainty and Expectation Revisions after Earnings Announcements* - Yeung, P. Eric (Contemporary Accounting Research, 2009)
Bayesian theory predicts an increase in market participants' reliance on reported current earnings to revise their expectations of future earnings when the uncertainty in future earnings is higher. Prior studies focus on price reactions and find negative associations between measures of earnings uncertainty and investors' reliance on reported current earnings. This study examines analysts' forecast revisions (of future earnings) around the announcements of current period earnings and finds positive associations between measures of earnings uncertainty and analysts' reliance on reported current earnings. The findings suggest that uncertainty measures and discount rates are correlated, and cross-sectional differences in the discount rate taint the interpretation of price reactions as evidence of expectation revisions under uncertainty. This study sheds additional light on the complex relationships among earnings uncertainty measures, price reactions to earnings surprise, and cost of capital.